Teknologi mutu tepung pisang dengan sistem spray drying untuk biskuit - Chasri Nurhayati; Oktavia Andayani (Jurnal Dinamika Penelitian Industri, 2014)
Bananas are a perishable commodity, necessitating further processing fluor substitution flour is a refined products used as a biscuits raw material diversification treatment. The hygienic way in the manufacture of bananas could be done by spray drying were utilize the hot temperatures of a blower This study used a fluor substitution kepok (A1) and fluor substitution. (A2) Having six variations of composition ratio of banana gedah flour, mung bean flour and fish fluor on treatment (P) were P1 (1: 1.5: 1.5), P2 (1: 1: 1), P3 (1: 0.5 : 0.5), P4 (2: 0.5: 0.5), P5 (3: 0.5: 0.5), P0 (4: 0: 0) Testing the quality standards of SNI 01- 3841-1995 of banana gedah flour based treatment and 01-7111.2-2005 The results showed that drying of banana gedah flour produced 3.62% water content for kepok fluor substitution bananas and 3.73% for fluor substitution bananas, met the the quality standards of SNI 01-3841-1995 with category A for quality. The best treatment on occured on A1P1 obtained by comparison 1: 1.5: 1.5 All biscuits treatment with bananas fluor substitution, fish flour and green bean flour met the quality requirements 01-7111.2-2005 except for the water content of banana gedah flour.Keywords: banana flour, spray drying, biscuitsAbstrakPisang merupakan komoditi bersifat mudah rusak, sehingga diperlukan pengolahan lanjutan. Tepung pisang merupakan produk olahan digunakan sebagai diversifikasi bahan baku biskuit. Cara hyangiene dalam pembuatan tepung dapat dilakukan dengan spray drying yaitu memanfaatkan suhu panas blower. Penelitian ini menggunakan pisang kepok (A1) dan pisang gedah (A2). Mempunyai enam variasi komposisi perbandingan tepung pisang, tepung kacang hijau dan tepung ikan pada substitusi biskuit (P) yaitu P1 (1:1,5 :1,5); P2 (1:1:1); P3 (1:0,5:0,5); P4 (2:0,5 :0,5); P5 (3:0,5:0,5); P0 (4:0:0). Pengujian tepung pisang berdasarkan standar mutu SNI 01-3841-1995 dan biskuit SNI 01-7111.2- 2005. Hasil penelitian menunjukkan pengeringan tepung pisang menghasilkan kadar air 3,62% untuk tepung pisang kepok dan 3,73% untuk tepung pisang gedah, memenuhi standar mutu SNI 01-3841-1995 kategori mutu A. Kandungan gizi biskuit terbaik diperoleh pada perlakuan A1P1 dengan perbandingan 1:1,5 :1,5. Semua perlakuan biskuit dengan substitusi tepung pisang , tepung ikan dan tepung kacang hijau memenuhi syarat mutu SNI 01-7111.2-2005 kecuali untuk kadar air biskuit tepung pisang gedah.Kata kunci: Tepung pisang, spray drying, biskuit